Experiencing historical buildings through digital computer games. (March 2018) - Şahbaz, Eray; Özköse, Aysun
This study aims to demonstrate the value of experiencing historical buildings through the digital game–based learning method. A three-dimensional computer game was developed to assess the digital game–based learning method as a supportive hypermedia tool in architectural education. The computer game features interactive game missions that enable students to get a close-up experience of the buildings. As part of the study, an experiment was conducted comparing the digital game–based learning method against other traditional methods in learning about historical buildings. The results of the study show that the digital game–based learning method can serve as a support for lecturing on historical buildings to help improve students' learning experience.